2015
DOI: 10.4236/jtr.2015.33015
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Sputum Specimen Samples Submitted for Culture and Drug Susceptibility Testing at the National Tuberculosis Reference Laboratory-Uganda, July-October 2013

Abstract: Setting: The Uganda National Tuberculosis Reference Laboratory (NTRL) in Kampala. Objective: The proportion of poor quality specimens received for drug susceptibility testing (DST) at the NTRL and factors contributing to poor specimen quality were assessed. Design: A cross-sectional study was conducted of sputum samples received at the NTRL from patients at high risk for multidrug-resistant tuberculosis (MDR TB) during July-October 2013. Demographic, clinical, and bacteriological data were abstracted from labo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…This means that for the majority of samples, the sample transportation worked well. A study in Uganda showed a different picture with 64% of samples being transported reported to be of poor quality; 16% were not triple packaged, 8% were <3 mls, 30% were not delivered on time, and 39% were salivary in appearance 13 . The use of different quality indicators in this study could partly explain the variation.…”
Section: Discussionmentioning
confidence: 99%
“…This means that for the majority of samples, the sample transportation worked well. A study in Uganda showed a different picture with 64% of samples being transported reported to be of poor quality; 16% were not triple packaged, 8% were <3 mls, 30% were not delivered on time, and 39% were salivary in appearance 13 . The use of different quality indicators in this study could partly explain the variation.…”
Section: Discussionmentioning
confidence: 99%